2008
DOI: 10.1590/s1806-37132008000900006
|View full text |Cite
|
Sign up to set email alerts
|

Estudo comparativo de sintomas respiratórios e função pulmonar em pacientes com doença pulmonar obstrutiva crônica relacionada à exposição à fumaça de lenha e de tabaco

Abstract: Comparative study of respiratory symptoms and lung function alterations in patients with chronic obstructive pulmonary disease related to the exposure to wood and tobacco smoke* Estudo comparativo de sintomas respiratórios e função pulmonar em pacientes com doença pulmonar obstrutiva crônica relacionada à exposição à fumaça de lenha e de tabaco AbstractObjective: To describe and analyze clinical symptoms and spirometric alterations of patients with chronic obstructive pulmonary disease (COPD) and history of e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
0
8

Year Published

2008
2008
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 14 publications
(26 reference statements)
3
15
0
8
Order By: Relevance
“…Although other studies have not found that the frequency of cough and sputum production is higher in women with wood smoke-related COPD than in those with smoking-related COPD, ( 23 , 24 ) probably because of differences in the degree of exposure or disease severity, previous studies conducted in Colombia have found that women exposed to wood smoke have a higher frequency of cough and expectoration, as well as increased bronchial hyperresponsiveness, which suggests greater airway involvement, a finding that is similar to that of the present study. ( 9 , 25 ) A study involving 86 patients with wood smoke-related COPD and 53 patients with smoking-related COPD, with different degrees of obstruction, found that the reduction in DLCO was less severe and was less correlated with the degree of obstruction (reduction in FEV 1 ) in the former than in the latter, and that the DLCO/VA ratio was normal in the former, ( 9 ) findings that are similar to those of the present study.…”
Section: Discussionmentioning
confidence: 86%
“…Although other studies have not found that the frequency of cough and sputum production is higher in women with wood smoke-related COPD than in those with smoking-related COPD, ( 23 , 24 ) probably because of differences in the degree of exposure or disease severity, previous studies conducted in Colombia have found that women exposed to wood smoke have a higher frequency of cough and expectoration, as well as increased bronchial hyperresponsiveness, which suggests greater airway involvement, a finding that is similar to that of the present study. ( 9 , 25 ) A study involving 86 patients with wood smoke-related COPD and 53 patients with smoking-related COPD, with different degrees of obstruction, found that the reduction in DLCO was less severe and was less correlated with the degree of obstruction (reduction in FEV 1 ) in the former than in the latter, and that the DLCO/VA ratio was normal in the former, ( 9 ) findings that are similar to those of the present study.…”
Section: Discussionmentioning
confidence: 86%
“…Although some studies show the exposure to smoke and the presence of more than one respiratory symptom (cough or dyspnea) as factors associated with COPD 1,3,4,8 , these variables did not show themselves to be associated in the group that was studied. The authors attribute this result possibly to limitations in memory due to those being treated are older people.…”
Section: Discussionmentioning
confidence: 85%
“…Amongst these risk factors classically discussed as associated with COPD, is that which has been highlighted namely smoking (being current or in the past) and the exposure to smoke such as from a wood stoves and coal 1,8 .…”
Section: Introductionmentioning
confidence: 99%
“…Geralmente as espécies que liberam odor forte ou fumaça escura são evitadas ou misturadas com J Sobre a influência da fumaça na saúde, a literatura científica possui diversos relatos onde a fumaça gerada pela queima de madeira é causadora ou potencializadora de doenças, como no caso da Doença Pulmonar Obstrutiva Crônica (DPOC) (Yaksic et al 2003;Godoy 2008;Moreira et al 2008).…”
Section: Resultsunclassified